2007
DOI: 10.1016/j.jbiomech.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Engineering controllable anisotropy in electrospun biodegradable nanofibrous scaffolds for musculoskeletal tissue engineering

Abstract: Many musculoskeletal tissues exhibit significant anisotropic mechanical properties reflective of a highly oriented underlying extracellular matrix. For tissue engineering, recreating this organization of the native tissue remains a challenge. To address this issue, this study explored the fabrication of biodegradable nanofibrous scaffolds composed of aligned fibers via electrospinning onto a rotating target, and characterized their mechanical anisotropy as a function of the production parameters. The character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
312
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 363 publications
(336 citation statements)
references
References 27 publications
16
312
1
1
Order By: Relevance
“…Previous studies suggested that cells appeared to favour a fibrous scaffold with a higher degree of alignment, in terms of cell alignment, proliferation, and extracellular matrix production [11,16]. However, less aligned fibre exhibited larger pore sizes, resulting in a higher number of cells attached, although in the longer term (7 and 14 days) the difference was not significant [16].…”
Section: Potential Application For Tissue Engineering Scaffoldmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies suggested that cells appeared to favour a fibrous scaffold with a higher degree of alignment, in terms of cell alignment, proliferation, and extracellular matrix production [11,16]. However, less aligned fibre exhibited larger pore sizes, resulting in a higher number of cells attached, although in the longer term (7 and 14 days) the difference was not significant [16].…”
Section: Potential Application For Tissue Engineering Scaffoldmentioning
confidence: 88%
“…It is also confirmed by other studies. Electrospinning using different mandrel rotation speeds (0 -8 m/s) showed that higher speeds produce fibres with higher alignment and tensile moduli, but yield lower ultimate strains [11]. One possible explanation is that it was due to fibre engagement at the beginning of deformation.…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The present study is therefore focused on engineering a tissue-like construct that will mimic the superficial zone of articular cartilage using bone marrow-derived human mesenchymal stem cells (hMSCs) and electrospun biocompatible polycaprolactone (PCL) scaffolds. Although several studies have been published to demonstrate that hMSCs or chondrocytes can be cultured on oriented electrospun nanofibrous scaffolds, 17,18 attempts to specifically engineer the superficial zone of the articular cartilage are currently lacking. Here we report that alignment and chondrogenic differentiation of hMSCs cultured on oriented electrospun PCL scaffolds are feasible and relatively easy to implement.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another challenge resides in the fact that a functional meniscal tissue must exhibit notable anisotropic mechanical properties resulting from a highly oriented underlying extracellular matrix [1]. In order to generate a scaffold which has controllable, anisotropic properties and mimicks meniscal extracellular matrix fiber alignment to direct fibrochondrocyte orientation electrospinning technology was used [25]. This technique is based on a biodegradable polymer and results in cartilage with about 20 % of the strength of native cartilage but with quite small pores that are difficult for chondrocytes to penetrate [3].…”
Section: Examples Of Novel Treatment Strategies In Animal Modelsmentioning
confidence: 99%